Novel cysteine-centered sulfur metabolic pathway in the thermotolerant methylotrophic yeast Hansenula polymorpha. - Min Jeong Sohn; Su Jin Yoo; Doo-Byoung Oh; Ohsuk Kwon; Sang Yup Lee; Andriy A Sibirny; Hyun Ah Kang (PLoS ONE, 2014)
In yeast and filamentous fungi, sulfide can be condensed either with O-acetylhomoserine to generate homocysteine, the precursor of methionine, or with O-acetylserine to directly generate cysteine. The resulting homocysteine and cysteine can be interconverted through transsulfuration pathway. Here, we systematically analyzed the sulfur metabolic pathway of the thermotolerant methylotrophic yeast Hansenula polymorpha, which has attracted much attention as an industrial yeast strain for various biotechnological applications. Quite interestingly, the detailed sulfur metabolic pathway of H. polymorpha, which was reconstructed based on combined analyses of the genome sequences and validation by systematic gene deletion experiments, revealed the absence of de novo synthesis of homocysteine from inorganic sulfur in this yeast. Thus, the direct biosynthesis of cysteine from sulfide is the only pathway of synthesizing sulfur amino acids from inorganic sulfur in H. polymorpha, despite the presence of both directions of transsulfuration pathway Moreover, only cysteine, but no other sulfur amino acid, was able to repress the expression of a subset of sulfur genes, suggesting its central and exclusive role in the control of H. polymorpha sulfur metabolism. 35S-Cys was more efficiently incorporated into intracellular sulfur compounds such as glutathione than 35S-Met in H. polymorpha, further supporting the cysteine-centered sulfur pathway. This is the first report on the novel features of H. polymorpha sulfur metabolic pathway, which are noticeably distinct from those of other yeast and filamentous fungal species.